IMPLEMENTASI LINGKUNGAN KAYA TEKS DI SATUAN PAUD UNTUK MENINGKATKAN PERKEMBANGAN BAHASA ANAK USIA DINI - Mutoharoh Mutoharoh; Euis Rusmalina (LPPM IAD Probolinggo, 2024)
This research aims to describe the implementation of a text-rich environment in PAUD units and its impact on children's language development. The research method used is qualitative with a case study approach. Research subjects at PAUD Shafa Marwah. Data collection was carried out through observation, interviews and documentation. The research results show that the implementation of a text-rich environment at PAUD Shafa Marwah has gone well. Children show high interest in the reading materials provided and actively interact with the text. This has a positive impact on children's language development, both in terms of vocabulary, reading comprehension and speaking ability. Keywords: Text-rich environment; language development; early childhood